The Effect of Radiotherapy on the Concentration of Plasma Lipids in Elderly Prostate Cancer Patients. Issue 2 (April 2019) - Wolny-Rokicka, Edyta; Tukiendorf, Andrzej; Wydmański, Jerzy; Brzezniakiewicz-Janus, Katarzyna; Zembroń-Łacny, Agnieszka
Lipids play an important role in processes such as the formation of membrane cells or in steroidogenesis, where androgens which stimulate the proliferation of prostate cancer (PCa) cells are produced. Previous studies presented links between cholesterol (CHOL) and PCa and concluded that cholesterol homeostasis changes in PCa patients during treatment and with age. This study further examines the correlation between the lipid profile, the treatment used, and the subjects' age. Ninety-one subjects (Group 1: >69 years; Group 2: ≤69) histopathologically diagnosed with PCa were tested. Total CHOL, triglycerides (TG), high-density lipoprotein (HDL), low density lipoprotein (LDL), and very low density lipoprotein (VLDL) were assessed from blood taken before the entire course of radiotherapy (RT) and in 3-month intervals after the treatment was completed, for up to 4 years (range: palliative and radical). In all the subjects, the CHOL decreased over time after RT ( p = .0445) with a simultaneous increase of prostate specific antigen (PSA) concentration ( p = .0366). A faster decrease of HDL was observed with a higher concentration of PSA ( p = .0053) and Gleason score ( p = .0304). In all the subjects, the HDL decreased after RT ( p = .0159) but in the older palliative group the HDL decrease progressed more slowly ( p = .0141). It could be stated, that after radical therapy TG levels tended to be consistently higher among younger men relative to the elderly ( p = .0151). But it was observed that RT treatment could lead to a decrease in the lipid serum concentration.